Socio-economic backgrounds of higher civil servants in the Philippines circa 1983 - Tapales, Proserpina D. (Philippine Journal of Public Administration, 1984)
The study underscores the political role of the bureaucracy by describing those at the apex of the bureaucracy composed of higher civil servants as the action group in political development. The socio-economic background of higher civil servants may be an important factor affecting this role. The study reveals the following findings. First, the urban bias in the recruitment of bureaucrats remains to date although this trend is gradually changing. Second, in terms of educational qualifications and family background, Filipino higher civil servants are better educated than their predecessors. This is a function of more and better educational opportunities available in the society. Third, an increasing number of younger women have entered the civil service in recent years, thus, indicating greater opportunities for them. Finally, the greater educational opportunities for younger women indicate greater access into the higher civil service.